Komunikasi Pemasaran Digital Campaign WhatsApp Blast di PT. Telkomsel branch Karawang Dalam Menarik Minat Konsumen - Rukmanah, Rukmanah; Dharta, Firdaus Yuni; Ema, Ema (Jurnal Ilmiah Wahana Pendidikan, 2023)
Marketing communication is a tool used by companies or business entities to inform, persuade, and remind consumers directly or indirectly about the products and brands being marketed. The use of WhatsApp blast is chosen as a digital medium in marketing activities in the digital era. The purpose of this research is to understand how advertising, specifically through the WhatsApp blast campaign, attracts consumer interest at PT. Telekomunikasi Selular branch Karawang through digital marketing communication. The theory employed in this study is the Integrated Marketing Communication (IMC) theory proposed by Don Schultz, introduced in 1998. The research utilizes qualitative research method with a descriptive approach. The results of this study indicate that PT. Telkomsel branch Karawang uses WhatsApp blast as an advertising medium to pique consumer interest in their products. PT. Telkomsel utilizes the WhatsApp blast feature to deliver promotional campaigns for Telkomsel products. This approach aligns with the IMC theory, which integrates various marketing communication channels to reach the appropriate target audience. By delivering compelling advertising messages and employing effective performance measurement, the company aims to create a more focused and successful marketing strategy.